1988
DOI: 10.1063/1.341191
|View full text |Cite
|
Sign up to set email alerts
|

Light-ion-bombarded p-type In0.53Ga0.47As

Abstract: Multiple-energy H-, He-, and B-ion bombardments were performed to obtain uniform high resistivity over the entire thickness of p-type In0.53Ga0.47As. High resistivity, 580 Ω cm, which is close to the intrinsic resistivity limit of ≊103 Ω cm in InGaAs, is observed. The thermal stability of the high-resistance layers depended upon the mass of the implanted ion. The B-ion-implanted layers maintained high resistivity up to ≊200 °C. Photoluminesence measurements were used to obtain the energy of compensating levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 21 publications
0
6
2
Order By: Relevance
“…For implants with O ϩ , C ϩ , and Li ϩ ions, there is a sharp rise in R s to its maximum at the critical dose D Cr with a relatively steep drop-off for higher doses. Rao et al 18 also found a very close compensation when implanting H, He, and B ions into p-InGaAs, although their maximum values of R s were one or two orders of magnitude lower than what we have achieved here. Moreover, Rao et al showed that for implants with these three ions, a kind of parallel decrease in R s occurred beyond the critical dose, which can also be seen for implants with O ϩ , C ϩ , and Li ϩ in Fig.…”
Section: Methodscontrasting
confidence: 56%
See 2 more Smart Citations
“…For implants with O ϩ , C ϩ , and Li ϩ ions, there is a sharp rise in R s to its maximum at the critical dose D Cr with a relatively steep drop-off for higher doses. Rao et al 18 also found a very close compensation when implanting H, He, and B ions into p-InGaAs, although their maximum values of R s were one or two orders of magnitude lower than what we have achieved here. Moreover, Rao et al showed that for implants with these three ions, a kind of parallel decrease in R s occurred beyond the critical dose, which can also be seen for implants with O ϩ , C ϩ , and Li ϩ in Fig.…”
Section: Methodscontrasting
confidence: 56%
“…A similar series of experiments was performed for 0.5-m n-InGaAs epilayers with carrier concentrations of 5ϫ10 16 , 2.7ϫ10 17 , and 1.2ϫ10 18 cm Ϫ3 . Figure 4 shows the corresponding results for implantation with C ϩ , O ϩ , Li ϩ , and H ϩ into samples with nϭ2.7ϫ10 17 cm Ϫ3 .…”
Section: B N-ingaasmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion implantation induced defects are often used as a beneficial processing step to control the lifetime and resistivity of ultrafast III-V optoelectronic switches 12,13 and materials. Although p to n-type conversion has been noted for ion implantation isolation studies in p-InGaAs, 22 the reverse has not been unambiguously observed although the Gill data certainly hints at it taking place. 15 Exactly how damage influences the high-speed performance of an InGaAs-InP detector will become an increasingly important issue, especially as links move to even higher speeds where constraints on bulk properties are tight.…”
Section: Simulation Of Impulse Response Degradation From Irradiation mentioning
confidence: 97%
“…Ion implantation has mostly been used to selectively create doped regions in the semiconductors such as the channel regions of FETs and the n + regions for source and drain contacts to FETs. Oxygen ion implantation in GaAs and InP for a generating semi-insulating layer has been studied for years [3][4][5][6]. The latter application is now gaining more attention.…”
Section: Introductionmentioning
confidence: 99%